Deteksi Virus Chikungunya pada nyamuk Aedes aegypti di Kabupaten Serdang Bedagai - Yoan Carolina Panggabean; Lia R Kusumawati; Hemma Yulfi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Chikungunya outbreak was reported in Indonesia on 1973 at Samarinda and DKI Jakarta. On 2000-2007, chikungunya outbreak occurred in all provinces with 18.169 cases without mortality in Indonesia. Now, almost all provinces in Indonesia are potential for chikungunya outbreak. Chikungunya is a disease caused by chikungunya virus, which is transmitted by mosquitoes Ae. aegypti. Some studies have been conducted to find out the chikungunya viral in some endemics area, however still few studies conducted in Sumatera Utara. The aim of this study was to find out chikungunya viral in mosquito of Ae. aegypti in four villages in District of Sergai. Minimum Infection Rate (MIR) is a measure of proportion of the mosquitoe population which is carrying a particular virus. When infection rate increases the risk of virus transmission to humans also increases.Method : This was a descriptive study for 50 samples of Ae. aegypti which were caught randomized from four villages of two endemis chikungunya subdistricts in district of Sergai then examined by using Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) technique to find out chikungunya virus. Chikungunya virus was examined by using TitanTM One Tube Reverse Transcriptase-Polymerace Chain Reaction RT-PCR) kit and CHIKnsP1-S sense primer (5’-TAG-GAC-AGG-AAA-TTGATC-CC-3’), CHIKnsP1-S anti-sense primer (5’-CTT-TAA-TCG-CCT-GGT-GGT-AT-3’). RT was running on temperature of 37C for an hour to gain cDNA, then amplifying by 35 recycling on temperature of 94oC for 3’, 94oC for 1’, 54oC for 90”, 54oC for 2’ and extension on temperature of 72oC for 2’.Result : 13 samples were positive for chikungunya virus from 50 samples which were examined. MIR was 130%.Conclusion : 13 samples which were found positive for chikungunya virus. MIR 130%, this was appropriate with high infection of chikungunya on patients where the mosquitoes were caught.Key words : Ae. aegypti, chikungunya virus, RT-PCR